Evaluation of Poor Eating Habits among Children Aged 3-16 Years in Schools - Yousaf, Ahmad Ibne; Gull, Zartasha; Affaf, Qaswara; Tahir, Sameen; Khattak, Kashif; Hussain, Azzah Khadim (Indus Journal of Bioscience Research, 2024)
In recent years, medical science has achieved significant advancements, yet nutrition remains a critical field with immense potential. Nutrition science, once underappreciated, gained recognition after global studies highlighted its vital role in combating health challenges. Today, with non-communicable diseases (NCDs) surpassing communicable diseases in prevalence, nutrition-based interventions are crucial. The global response includes initiatives by organizations like WHO, FAO, and UNICEF, which invest billions in programs such as food fortification and nutrition education. According to 2020 Joint Child Malnutrition Estimates, 149.2 million children under five were stunted, 45.4 million wasted, and 38.9 million overweight. COVID-19 exacerbated nutrition challenges, especially in South Asia, where awareness is limited. The pandemic underscored the link between nutrition and immunity, prompting renewed focus on dietary interventions. In Pakistan, malnutrition, stunting, and anemia remain prevalent. Our study examines the factors driving poor nutrition, focusing on the eating habits of children aged 3–16 in Peer-Mahil, District Toba Tek Singh, Punjab. Collaborating with NutriBites, we surveyed 500 children (255 boys, 245 girls) using anthropometric measurements, clinical assessments, questionnaires, and discussions. Data was analyzed via SPSS, revealing significant trends in dietary behaviors and nutritional deficiencies. This report highlights the urgent need for multidimensional public nutrition policies to address these issues and improve child health outcomes in Pakistan.